41.2k views
0 votes
Solve for the x using elimination
3x-2y=13x−2y=1
2x+2y=42x+2y=4

User WJA
by
5.4k points

1 Answer

3 votes

3x - 2y = 1

2x + 2y = 4

Add the second equation to the first

5x = 5

2x + 2y = 4

Divide the first equation by 5

x = 1

2x + 2y = 4

Subtract the first equation from the second

x = 1

x + 2y = 3

Subtract the first equation from the second again

x = 1

2y = 2

Divide the second equation by 2

x = 1

y = 1

So, the solution is x = 1 and y = 1 {or: (1, 1)}

User Shivkumar
by
5.2k points